Flexible wearable power generation device and preparation method thereof

By forming an asymmetric atomic layer deposition functional film layer and a PVA cross-linked polypyrrole structure on the conductive non-woven fabric layer, the problems of low efficiency and insufficient stability of moisture power generation devices are solved, and stable power output and efficient power generation are achieved in complex environments, which is suitable for smart wearable devices.

CN120710380APending Publication Date: 2025-09-26HUBEI ENG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510673961.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-23
Publication Date
2025-09-26

AI Technical Summary

Technical Problem

Existing wet gas power generation devices have low power generation efficiency, insufficient stability and reliability, and are difficult to meet the high energy consumption requirements of smart wearable devices. In addition, their performance is unstable in complex environments.

Method used

An asymmetric structure of a conductive non-woven fabric layer and an atomic layer deposition functional film layer is adopted, combined with PVA cross-linked polypyrrole conductive material, and ALD technology is used to form an ultra-thin, uniform Al2O3 film on the conductive non-woven fabric layer to enhance the electrochemical asymmetry and interfacial bonding force, and generate electricity through photothermal evaporation humidity gradient.

Benefits of technology

It achieves stable and continuous power output in different environments, has excellent water-wash resistance, biocompatibility and antibacterial ability, and is suitable for smart wearable devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120710380A_ABST
    Figure CN120710380A_ABST
Patent Text Reader

Abstract

The invention provides a flexible wearable power generation device and a preparation method thereof, and belongs to the technical field of flexible power generation, the flexible wearable power generation device comprises a conductive non-woven fabric layer and an atomic layer deposition functional film layer attached to one side of the conductive non-woven fabric layer, the projection area of the atomic layer deposition functional film layer on the conductive non-woven fabric layer is smaller than the area of the conductive non-woven fabric layer; and a heat absorption difference exists between the conductive non-woven fabric layer and the atomic layer deposition functional film layer for solar radiation. The flexible wearable power generation device prepared by the invention has excellent washing resistance, biocompatibility and antibacterial ability, and has stable voltage and current output.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of flexible power generation technology, and in particular to a flexible wearable power generation device and a preparation method thereof. Background Art

[0002] In recent years, the global overconsumption of non-renewable energy has triggered a severe energy crisis, prompting researchers to actively explore alternative strategies for generating electricity. With energy demand continuing to rise and environmental protection receiving significant attention, the development of sustainable, clean energy has become a pressing need. As a key branch of hydrovoltaic power generation, wet gas power generation, which utilizes water vapor, a widely available atmospheric resource, as its energy source, has gradually gained attention, demonstrating significant research value and broad application prospects.

[0003] Moisture, a vital component of Earth's water cycle, holds enormous potential for energy, yet has long been underutilized. Unlike traditional, large-scale hydropower generation, wet gas power generation focuses on the interaction between water molecules and functional materials at the microscopic level, leveraging the physical and chemical properties of the material's surface to convert energy into electricity. With the rapid growth of the smart wearable device market, the demand for compact, efficient, and sustainable energy sources compatible with these devices is becoming increasingly urgent. Smart wearable devices such as smart watches, smart bracelets, and health monitoring patches not only bring significant convenience to people's lives but also play a key role in healthcare, fitness monitoring, and information exchange. However, these devices currently rely primarily on batteries with limited battery life, and frequent charging has become a bottleneck hindering their further development. Wet gas power generation, which can continuously generate electricity from ambient moisture, holds promise as an ideal power supply solution for smart wearable devices.

[0004] However, wet gas power generation technology still faces many challenges on its road to practical application. First, the power generation efficiency of wet gas power generation devices is generally low, and there is a significant gap between their output power and energy conversion efficiency and traditional energy sources. In practical applications, it is difficult to meet the growing high energy consumption needs of smart wearable devices. Secondly, the materials and device structures used for wet gas power generation urgently need to be optimized. Existing materials have limited ability to adsorb and convert moisture into charge, and it is necessary to continuously explore new nanomaterials and unique device structures to enhance the interaction between water molecules and materials and improve power generation performance. Furthermore, wet gas power generation devices lack stability and reliability under complex and changing environmental conditions. Smart wearable devices have a wide variety of usage scenarios, and factors such as environmental humidity, temperature, and wind speed will affect the effect of wet gas power generation. Therefore, there is an urgent need to develop a new power generation device to ensure that the power generation device can output electricity stably and continuously under different environments. Summary of the Invention

[0005] In view of the technical problems existing in the background technology, the present invention provides a flexible wearable power generation device and a preparation method thereof, aiming to solve the technical problems of low output power and energy conversion efficiency, and insufficient stability and reliability of existing moisture power generation devices.

[0006] In a first aspect, the present invention provides a flexible wearable power generation device, comprising a conductive non-woven fabric layer and an atomic layer deposition functional film layer adhered to one side of the conductive non-woven fabric layer, wherein the projected area of ​​the atomic layer deposition functional film layer on the conductive non-woven fabric layer is smaller than the area of ​​the conductive non-woven fabric layer; there is a heat absorption difference between the conductive non-woven fabric layer and the atomic layer deposition functional film layer to solar radiation.

[0007] Preferably, the projected area of ​​the atomic layer deposition functional thin film layer on the conductive non-woven fabric layer is 1 / 3 to 2 / 3 of the area of ​​the conductive non-woven fabric layer.

[0008] Preferably, the projected area of ​​the atomic layer deposition functional thin film layer on the conductive non-woven fabric layer is 1 / 2 of the area of ​​the conductive non-woven fabric layer.

[0009] Preferably, the structural color of the atomic layer deposition functional thin film layer is different from the structural color of the conductive non-woven fabric layer.

[0010] Preferably, the thickness of the atomic layer deposition functional thin film layer is 10-100 nm.

[0011] More preferably, the thickness of the atomic layer deposition functional thin film layer is 80 nm.

[0012] Preferably, the conductive material of the conductive non-woven fabric layer includes polypyrrole cross-linked with polyvinyl alcohol.

[0013] Preferably, the flexible wearable power generation device further includes a skin-friendly adhesion layer, which is adhered to the side of the conductive non-woven fabric layer away from the atomic layer deposition functional thin film layer.

[0014] In the present invention, the material of the skin-friendly contact layer includes but is not limited to the non-woven fabrics listed in the embodiments of the present invention. Those skilled in the art can select other materials with properties such as softness, breathability, moisture absorption and perspiration removal, and low allergenicity according to actual conditions.

[0015] In a second aspect, the present invention provides a method for preparing a flexible wearable power generation device, comprising the following steps: S1, pre-treating the non-woven fabric, then mixing it with a pyrrole solution, adding an oxidant to react in an ice bath, washing and drying it, then immersing it in a PVA solution, heating and cross-linking it, to obtain a conductive non-woven fabric layer; S2. Performing a single-sided atomic layer deposition process on the conductive non-woven fabric layer to obtain an atomic layer deposition functional thin film layer.

[0016] Preferably, in step S1, the non-woven fabric includes at least one of PLA non-woven fabric, polypropylene non-woven fabric, polyester non-woven fabric, and viscose fiber non-woven fabric.

[0017] Preferably, in step S1, the pretreatment specifically comprises: ultrasonically cleaning and drying the non-woven fabric with an organic solvent, wherein the organic solvent comprises at least one of anhydrous ethanol, methanol, and propanol; The oxidant comprises at least one of ammonium persulfate, ferric chloride, potassium permanganate, and chloranil; The ice bath temperature is 0~10℃ and the reaction time is 3~5h; The temperature for heating cross-linking is 110-130° C., and the time for heating cross-linking is 20-40 minutes.

[0018] Preferably, the single-sided atomic layer deposition process is specifically as follows: placing the conductive non-woven fabric layer in the atomic layer deposition equipment, evacuating the vacuum, and setting the deposition temperature at the same time. After the temperature stabilizes, the deposition cycle is started. After the deposition is completed, it is cooled to room temperature, and the sample is taken out to obtain an atomic layer deposition functional thin film layer; one deposition cycle includes: precursor A pulse 0.05~0.2 s, nitrogen purge 5~15 s, precursor B pulse 0.05~0.2 s, nitrogen purge 5~15 s.

[0019] Preferably, the vacuuming is to vacuumize to a vacuum degree of 1×10 -6 ~1×10 -8 Torr; the deposition temperature is 80~150℃, and the number of deposition cycles is 100~1500 times; Precursor A includes at least one of trimethylaluminum (TMA), titanium tetrachloride (TiCl4), and diethylzinc (DEZ); more preferably trimethylaluminum (TMA); The precursor B includes at least one of deionized water, ozone, ammonia, and hydrazine; more preferably, deionized water.

[0020] Preferably, step S2 further includes step S3: laminating the skin-friendly bonding layer to the side of the conductive non-woven fabric layer away from the atomic layer deposition functional film layer, and performing stitching, hot pressing and packaging to obtain the flexible wearable power generation device.

[0021] The principle of the technical solution of the present invention is as follows: The asymmetric structure of the color of the conductive non-woven fabric layer and the atomic layer deposition functional film layer partially covering the surface of the conductive non-woven fabric layer forms a difference in evaporation rate under sunlight, so that a difference in humidity is formed at both ends of the conductive non-woven fabric layer and the atomic layer deposition functional film layer. This humidity difference drives the diffusion of water molecules, thereby generating an electric potential difference between the two, forming an electric current, and realizing the power generation function. At the same time, the conductive material of the conductive non-woven fabric middle layer used in the present invention is PVA cross-linked polypyrrole, which has specific electrochemical properties. The atomic layer deposition functional film layer also has its own electrochemical characteristics, and the two will form electrochemical asymmetry when in contact. This electrochemical asymmetry can also promote the transfer of electrons, further enhancing the power generation effect.

[0022] Atomic layer deposition (ALD) technology precisely controls film thickness at the atomic level, adding only one atomic layer per deposition. This high precision enables ALD to produce ultra-thin and uniform films. ALD-deposited films are remarkably uniform, pinhole-free, and possess excellent sealing and isolation properties, effectively inhibiting the growth of various bacteria and enhancing antibacterial capabilities. ALD technology enables selective deposition on different surface areas by precisely controlling the introduction of reactive gases and reaction conditions. Chemical adsorption of the ALD precursor to the substrate surface ensures excellent adhesion, enabling the film to maintain good adhesion to the substrate.

[0023] Compared with the prior art, the present invention has the following advantages and beneficial effects: (1) The flexible wearable power generation device prepared by the present invention has excellent water-washing resistance. It uses a combination of special materials and advanced technology to make the non-woven fabric structure compact and stable. Even after frequent water washing, the output of various electrical signals remains stable, and there will be no power failure or malfunction. It can always maintain the use effect of new, providing users with a long-term and stable use experience.

[0024] (2) The flexible wearable power generation device prepared by the present invention exhibits excellent biocompatibility and strong antibacterial ability. It is made of skin-friendly and harmless materials. When in contact with human skin, it will not cause allergies or other discomfort reactions and can fit the skin perfectly. At the same time, ALD technology gives it high antibacterial ability, which can effectively inhibit the growth of various bacteria and keep the non-woven fabric clean and hygienic, allowing users to wear it comfortably while also obtaining health protection.

[0025] (3) The output performance of smart wearable fabrics is stable and long-lasting. Its internal energy supply system is derived from the moisture in the environment. After careful design and optimization, it can continuously provide stable power output during long-term use. With only minor fluctuations in the external environment or long-term operation, it can provide users with reliable service.

[0026] (4) The present invention belongs to clean energy. Its preparation method is simple, easy to operate, has high production efficiency, is biodegradable, has low energy consumption, and is easy to obtain energy sources. Its use has low environmental requirements and can be produced on a large scale and in large quantities. It has great application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a schematic diagram of a flexible wearable power generation device prepared in Example 1 of the present invention; Figure 2 Vt graphs and It graphs of the flexible wearable power generation devices prepared in Examples 1 to 3 of the present invention and Comparative Example 1 measured at the same temperature and humidity; Figure 3 The conductivity diagram of the flexible wearable power generation device prepared in Examples 1 to 3 of the present invention and Comparative Example 1 measured at the same temperature and humidity; Figure 4 This is a temperature curve diagram of the flexible wearable power generation device prepared in Examples 1 to 3 of the present invention and Comparative Example 1 measured at the same humidity; Figure 5 Absorption spectra of the flexible wearable power generation devices prepared in Examples 1 to 3 of the present invention and Comparative Example 1; Figure 6 This is a graph showing the number of water washing cycles of the flexible wearable power generation device prepared in Example 1 of the present invention; Figure 7 This is an inhibition zone diagram of the flexible wearable power generation device prepared in Example 1 of the present invention; Figure 8 This is a diagram showing the practical application of the flexible wearable power generation device prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0028] The following embodiments of the technical solution of the present invention will be described in detail with reference to the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention and are therefore only examples and are not intended to limit the scope of protection of the present invention.

[0029] The present invention provides a flexible wearable power generation device, comprising a conductive non-woven fabric layer and an atomic layer deposition functional film layer adhered to one side of the conductive non-woven fabric layer, wherein the projected area of ​​the atomic layer deposition functional film layer on the conductive non-woven fabric layer is smaller than the area of ​​the conductive non-woven fabric layer; there is a heat absorption difference between the conductive non-woven fabric layer and the atomic layer deposition functional film layer to solar radiation.

[0030] In some embodiments, the projected area of ​​the atomic layer deposition functional thin film layer on the conductive non-woven fabric layer is 1 / 3 to 2 / 3 of the area of ​​the conductive non-woven fabric layer; more preferably, the projected area of ​​the atomic layer deposition functional thin film layer on the conductive non-woven fabric layer is 1 / 2 of the area of ​​the conductive non-woven fabric layer.

[0031] In some embodiments, the conductive material of the conductive non-woven fabric layer includes polypyrrole cross-linked with polyvinyl alcohol.

[0032] In some embodiments, the thickness of the atomic layer deposition functional thin film layer is 10-100 nm, more preferably 80 nm.

[0033] In some embodiments, the structural color of the atomic layer deposition functional thin film layer is different from the structural color of the conductive non-woven fabric layer.

[0034] In the present invention, structural color refers to a color that can reflect light of a specific wavelength.

[0035] In the present invention, the structural color of the atomic layer deposition functional thin film layer is a color having a different absorbance from black in the wavelength range of 0.5μm to 2.5μm, including but not limited to red, yellow, green, and blue.

[0036] In some embodiments, the flexible wearable power generation device further includes a skin-friendly adhesion layer, which is adhered to the side of the conductive non-woven fabric layer away from the atomic layer deposition functional thin film layer.

[0037] In the present invention, the material of the skin-friendly contact layer includes but is not limited to the non-woven fabrics listed in the embodiments of the present invention. Those skilled in the art can select other materials with properties such as softness, breathability, moisture absorption and perspiration removal, and low allergenicity according to actual conditions.

[0038] The present invention provides a method for preparing a flexible wearable power generation device, comprising the following steps: S1, pre-treating the non-woven fabric, then mixing it with a pyrrole solution, adding an oxidant to react in an ice bath, washing and drying it, then immersing it in a PVA solution, heating and cross-linking it, to obtain a conductive non-woven fabric layer; S2. Performing a single-sided atomic layer deposition process on the conductive non-woven fabric layer to obtain an atomic layer deposition functional thin film layer.

[0039] In some embodiments, the non-woven fabric includes at least one of PLA non-woven fabric, polypropylene non-woven fabric, polyester non-woven fabric, and viscose fiber non-woven fabric; more preferably, the non-woven fabric is PLA non-woven fabric.

[0040] In some embodiments, step S1 is specifically as follows: cutting the non-woven fabric into a 10 cm × 10 cm square pattern, then placing the sample in an ultrasonic cleaning machine, adding an appropriate amount of organic solvent, and ultrasonically cleaning for 15 to 30 minutes to remove surface oil and impurities, and then rinsing with deionized water 3 to 5 times, and then placing the cleaned non-woven fabric in a vacuum drying oven, drying at 50 to 70 ° C for 3 to 5 hours to constant weight to obtain a pretreated non-woven fabric; the organic solvent includes at least one of anhydrous ethanol, methanol, and propanol, preferably anhydrous ethanol; The pretreated non-woven fabric is placed in a three-necked flask containing a pyrrole solution, stirred under ice bath conditions, and an oxidant is slowly added dropwise using a constant pressure dropping funnel. After the addition is completed, the reaction is continued under ice bath conditions while maintaining uniform stirring. After the reaction is completed, the non-woven fabric is taken out and repeatedly rinsed with deionized water until the washing liquid is colorless, and then dried in a vacuum drying oven to obtain a non-woven fabric loaded with polypyrrole. The non-woven fabric loaded with polypyrrole is immersed in a PVA solution at room temperature, taken out and gently absorbed with filter paper to remove excess solution on the surface, and then placed in an oven for heating and cross-linking. The cross-linked non-woven fabric is rinsed with deionized water to remove unreacted PVA, and then dried in a vacuum drying oven. After taking out, a conductive non-woven fabric can be obtained.

[0041] In some embodiments, in step S1, the pyrrole solution is prepared by adding 0.39-1.56 g of pyrrole monomer (Py) to 100 mL of deionized water and stirring to dissolve the resulting aqueous solution; more preferably, 0.957 g of pyrrole monomer (Py) is added to 100 mL of deionized water and stirred to dissolve the resulting aqueous solution; the polyvinyl alcohol (PVA) solution is prepared by weighing 1-5 g of PVA and adding it to 100 mL of deionized water, preferably 2.5 g of PVA and adding it to 100 mL of deionized water, and heating and stirring in a water bath at 80-95°C at a speed of 300-500 r / min for 1-3 hours to completely dissolve the PVA.

[0042] In some embodiments, in step S1, the ice bath temperature is 0-10°C, and the stirring time under the ice bath is 20-40 minutes; the oxidant is at least one of ammonium persulfate, ferric chloride, potassium permanganate, and tetrachlorobenzoquinone; more preferably ammonium persulfate; the dripping rate of the constant pressure dropping funnel is 1-2 drops / second, and after the dropwise addition is completed, the reaction is continued in the ice bath for 3-5 hours, during which the stirring speed is maintained at 200-400 r / min; the soaking time in PVA is 0.5-2 hours; the heating cross-linking temperature is 110-130°C, and the cross-linking time is 20-40 minutes; the drying temperature is 50-70°C, and the drying time is 3-5 hours.

[0043] In the present invention, polypyrrole is cross-linked with PVA, a flexible polymer material whose hydroxyl groups (-OH) on the molecular chain can form an interpenetrating network structure with polypyrrole through hydrogen bonding or chemical cross-linking. This cross-linking can tightly bind the brittle polypyrrole conductive layer to the flexible PVA matrix, improving the overall mechanical strength of the composite material. The PVA cross-linked network serves as a supporting skeleton, fixing the conductive particles of polypyrrole and preventing them from migrating or agglomerating due to external forces or environmental changes (such as humidity and friction). The dense network structure can also block the erosion of polypyrrole by external environmental factors such as water vapor and oxygen. The PVA solution penetrates into the gaps between the fibers of the polypyrrole-modified non-woven fabric, forming a continuous three-dimensional structure through cross-linking, thereby strengthening the bonding between the polypyrrole and the non-woven fabric substrate.

[0044] In some embodiments, step S2 is specifically as follows: placing the conductive non-woven fabric layer in an atomic layer deposition (ALD) device, evacuating to a certain vacuum degree, setting the deposition temperature at the same time, and starting the deposition cycle after the temperature stabilizes. After the deposition is completed, cooling to room temperature, taking out the sample, and obtaining an atomic layer deposition functional thin film layer; one deposition cycle includes: a precursor A pulse of 0.05~0.2 s, a nitrogen purge of 5~15 s, a precursor B pulse of 0.05~0.2 s, and a nitrogen purge of 5~15 s.

[0045] In some embodiments, in step S2, the vacuum degree is 1×10 -6 ~1×10 -8 Torr; the deposition temperature is 80~150℃, and the number of deposition cycles is 100~1500 times; the precursor A includes at least one of trimethylaluminum (TMA), titanium tetrachloride (TiCl4), and diethylzinc (DEZ); more preferably trimethylaluminum (TMA); the precursor B includes at least one of deionized water, ozone, ammonia, and hydrazine; more preferably deionized water.

[0046] The selection of precursors A (TMA, TiCl₄, DEZ) and B (H₂O, O₃, etc.) is based on their chemical reaction characteristics, film-forming properties, and compatibility with flexible substrates. The TMA+H₂O combination is preferred because it produces ultrathin, dense, and highly barrier Al₂O₃ films at low temperatures. This perfectly balances the flexibility, durability, and functionality requirements of wearable power generation devices while also being feasible and economical for industrial production. TMA is a classic precursor for depositing aluminum oxide (Al₂O₃). The aluminum atoms in its molecule undergo a self-limiting reaction with hydroxyl groups (-OH) on the substrate surface, forming a monolayer of Al-O bonds and releasing methane (CH₄). The reaction equation is: 2A₁(CH₃)₃+3H₂O→A₁₂O₃+6CH₄. TMA exhibits high reactivity at temperatures between 80 and 150°C, making it suitable for low-temperature processes on flexible substrates such as nonwovens. The resulting Al₂O₃ film is pinhole-free, effectively blocking water and oxygen, and protecting the polypyrrole conductive layer from environmental corrosion. Moreover, the thickness of the Al2O3 film is controllable (100~1500 cycles correspond to about 10~150nm), which can maintain the flexibility of the substrate; in addition, the dense Al2O3 film can also inhibit bacterial adhesion and improve wearing hygiene.

[0047] In this invention, ALD technology is used to precisely control the thickness of the film at the atomic level, with each deposition adding only one atomic layer. This high precision enables ALD to produce ultra-thin and uniform films. ALD-deposited films are remarkably uniform, with no pinholes on the surface, and possess excellent sealing and isolation properties, effectively inhibiting the growth of various bacteria and enhancing antibacterial capabilities. ALD technology enables selective deposition on different surface areas by precisely controlling the introduction of reactive gases and reaction conditions. Chemical adsorption of the ALD precursor to the substrate surface ensures excellent adhesion, enabling the film to maintain good bonding to the substrate. ALD reactions are typically performed at low temperatures (50-200°C) to avoid thermal damage to flexible substrates (such as non-woven fabrics and PVA) caused by high temperatures.

[0048] In some embodiments, step S2 further includes step S3: laminating the skin-friendly bonding layer to the side of the conductive non-woven fabric layer away from the atomic layer deposition functional film layer, and performing stitching, hot pressing and packaging to obtain the flexible wearable power generation device.

[0049] In some embodiments, step S3 is specifically as follows: aligning the length and width of the skin-friendly bonding layer and the side of the conductive non-woven fabric layer away from the atomic layer deposition functional film layer, using a sewing machine to sew along the edge, controlling the needle distance, ensuring that the suturing is firm, and then performing hot pressing and packaging to obtain a flexible wearable power generation device.

[0050] In some embodiments, in step S3, the suture thread includes at least one of polyester thread, nylon thread, cotton thread, and silk thread, preferably polyester thread; the stitch length is controlled at 0.3~0.7 cm to ensure that the suture is firm, preferably 0.5 cm; the hot pressing temperature is 80°C, the pressure is 0.5 MPa, and the time is 5 minutes; the packaging treatment is: apply a thin layer of PU glue on the suture area and cure at 60°C for 1 hour.

[0051] The present invention is further described below through specific examples.

[0052] In the following examples of the present invention, the non-woven fabric used was from Zhejiang Haili Environmental Protection Technology, the drugs used were from Sinopharm Group Co., Ltd., the precursors used were from Nanjing Aike Fine Chemicals, and the polyester fiber line was from Jiangsu Hengli Chemical Fiber.

[0053] The pyrrole (Py) solution was prepared as follows: 0.957 g of pyrrole was added to 100 ml of deionized water and stirred at 300-500 rpm for 15 minutes.

[0054] The ammonium persulfate (APS) solution (oxidant) used was prepared as follows: 1.71 g of ammonium persulfate was added to 100 ml of deionized water and stirred at a speed of 300-500 r / min for 15 min.

[0055] The preparation method of the PVA solution used is as follows: 2.5 g of polyvinyl alcohol (PVA1750±50, alcoholysis degree 99%) is added to 100 mL of deionized water and dissolved evenly to obtain a 2.5 w / v% PVA solution.

[0056] The nonwoven fabric used is a polylactic acid (PLA) nonwoven fabric with a grammage range of 50 g / m².

[0057] 1. Preparation method Example 1 A method for preparing a flexible wearable power generation device comprises the following steps: (1) Pretreatment of non-woven fabric: PLA (polylactic acid) non-woven fabric was cut into 10 × 10 cm square samples. The samples were then placed in an ultrasonic cleaning machine, 50 mL of anhydrous ethanol was added, and ultrasonic cleaning was performed for 20 minutes to remove surface oil and impurities. The samples were then rinsed with deionized water 5 times and dried in a vacuum drying oven at 60 °C for 4 hours to obtain pretreated PLA non-woven fabric. (2) Preparation of conductive non-woven fabric: The pretreated PLA non-woven fabric was placed in a three-necked flask containing pyrrole solution and stirred for 30 minutes under ice bath conditions (5°C) to allow pyrrole to be fully adsorbed on the surface of the non-woven fabric. Ammonium persulfate (APS) solution was added to the three-necked flask at a rate of 1-2 drops / second using a constant pressure dropping funnel. After the addition was completed, the reaction continued for 4 hours under ice bath conditions, during which the stirring speed was maintained at 350r / min. After the reaction was completed, it was repeatedly rinsed with deionized water until the washing liquid was colorless, and then dried in a vacuum drying oven at 60°C for 4 hours to obtain PLA non-woven fabric loaded with polypyrrole; the PLA non-woven fabric loaded with polypyrrole was placed in a PVA solution and soaked at room temperature for 1.5 hours. After taking it out, the excess solution on the surface was gently absorbed with filter paper, and then placed in an oven and heated at 120°C for cross-linking for 30 minutes. After cross-linking, it was rinsed with deionized water 4 times to remove unreacted PVA, and then dried in a vacuum drying oven at 60°C for 4 hours to obtain a black conductive non-woven fabric; (3) Preparation of atomic layer deposition functional thin film layer: Place 1 / 2 of the size of the conductive non-woven fabric into the reaction chamber of the ALD (atomic layer deposition) equipment, place the sample flat, close the reaction chamber door and evacuate to 1×10 -7 Torr, set the deposition temperature to 100°C, and after the temperature stabilized, start the deposition cycle; one deposition cycle includes: TMA (trimethylaluminum) pulse 0.05 s, nitrogen purge 15 s, deionized water pulse 0.05 s, nitrogen purge 15 s; set the number of deposition cycles to 800. After the deposition is completed, wait for the reaction chamber to cool to room temperature and remove the sample. At this time, the film thickness is about 80nm, and the black conductive non-woven fabric surface shows a purple atomic layer deposition functional film layer; (4) Preparation of a flexible wearable power generation device: The non-woven fabric pretreated in step (1) and the side of the conductive non-woven fabric not subjected to atomic layer deposition in step (3) are laminated and precisely aligned, the edges are fixed with a traceless clip, and the edges are sutured with a polyester fiber thread at a stitch length of 0.5 cm. Subsequently, a hot pressing treatment is performed at 80°C, 0.5 MPa, and 5 minutes to enhance the interlayer bonding. Finally, a thin layer of PU glue is applied to the sutured area and cured at 60°C for 1 hour to obtain a flexible wearable power generation device, which is recorded as a "purple non-woven fabric" flexible wearable power generation device.

[0058] Figure 1 Schematic diagram of the flexible wearable power generation device prepared in Example 1 of the present invention.

[0059] Example 2 This embodiment provides a method for preparing a flexible wearable power generation device. The difference from Example 1 is that the number of deposition cycles set in step (3) of this embodiment when preparing the atomic layer deposition functional thin film layer is 450 times. After the deposition is completed, the reaction chamber is cooled to room temperature and the sample is taken out. At this time, the film thickness is about 45 nm, and the surface of the black conductive non-woven fabric presents a golden atomic layer deposition functional thin film layer, thereby obtaining a flexible wearable power generation device, which is recorded as a "golden non-woven fabric" flexible wearable power generation device.

[0060] Example 3 This embodiment provides a method for preparing a flexible wearable power generation device. The difference from Example 1 is that in step (3) of this embodiment, an atomic layer deposition functional thin film layer is prepared, and the number of deposition cycles is set to 1300. After the deposition is completed, the reaction chamber is cooled to room temperature and the sample is removed. At this time, the film thickness is about 120 nm, and the surface of the black conductive non-woven fabric presents a green atomic layer deposition functional thin film layer, thereby obtaining a flexible wearable power generation device, which is recorded as a "green non-woven fabric" flexible wearable power generation device.

[0061] Comparative Example 1 This comparative example provides a method for preparing a flexible wearable power generation device. The only difference from Example 1 is that in this comparative example: step (3) is omitted, and only steps (1), (2) and (4) are performed. The obtained flexible wearable power generation device is recorded as a "black non-woven fabric" flexible wearable power generation device.

[0062] Comparative Example 2 This comparative example provides a method for preparing a flexible wearable power generation device. The only difference from Example 1 is that in this comparative example: in step (3), the entire conductive non-woven fabric is placed in the reaction chamber of the ALD (atomic layer deposition) equipment, and the atomic layer deposition parameters are set the same as in Example 1 to obtain a flexible wearable power generation device, which is recorded as an "all-purple non-woven fabric" flexible wearable power generation device.

[0063] Comparative Example 3 This comparative example provides a method for preparing a flexible wearable power generation device. The only difference from Example 1 is that in this comparative example: in step (2), the PLA non-woven fabric loaded with polypyrrole is not placed in the PVA solution for cross-linking reaction.

[0064] 2. Test Method The flexible wearable power generation devices obtained in each embodiment and comparative example were subjected to performance tests, including the following: (1) Electrical signal change test: Measurements were made using an electrochemical workstation (CHI660E). The positive and negative electrodes were connected to the conductive nonwoven fabric layer of the flexible wearable power generation device. Data were recorded after 1 minute, once the voltage and current stabilized. The ambient temperature during voltage measurement was 30-40°C and the relative humidity was 56%-62%.

[0065] (2) Conductivity test: The electrical conductivity at different locations on the sample surface was measured using a four-probe tester to evaluate the uniformity of polypyrrole loading and the conductive properties.

[0066] (3) Thermocouple test: K-type thermocouple sensors were placed at the bottom of the flexible wearable power generation device to test the temperature of the flexible wearable power generation device. A two-channel temperature recorder (TA612C) was used to record the real-time temperature. A xenon lamp (CELHXF300, Education Au-light) was placed 30 cm above the generator device to simulate sunlight. The xenon lamp irradiated the surface of the flexible wearable power generation device vertically with a light intensity of 1 kW / m 2 To shield the impact of heat convection, a layer of polyethylene film was covered on the flexible wearable power generation device. The relative humidity of the environment was 56% to 62% when the temperature was measured.

[0067] (4) Solar radiation absorption test: The sample was scanned using an integrating sphere UV-visible spectrophotometer (UV-3600plus) for 2 min with a scanning step of 2 nm.

[0068] (4) Washing resistance test: The flexible wearable power generation device was placed in a washing machine and washed at 40°C for 30 minutes according to GB / T 3921-2008 standard. This was repeated five times, and the resistance change rate was tested.

[0069] (5) Antibacterial test: The flexible wearable power generation device was cut into discs with a diameter of 5 mm and a thickness of 4 mm. Six copies were prepared. Before the test, the sample was soaked in 75% ethanol solution for 1 minute, rinsed with sterile water, and dried naturally. The experimental temperature was controlled at (37 ± 1) °C, the relative humidity was greater than 90% RH, and the test strain was Staphylococcus aureus CGMCC 1.89. Take 0.3 mL of bacterial suspension and spread it evenly on the NA plate with a coating stick. The concentration of the bacterial suspension was 10 6 ~10 8CFU / mL. Use sterile, dry filter paper with a diameter of 5 mm as a control sample. Add 20 μL of sterile distilled water to each piece of filter paper, dry it, and then sterilize it with high pressure heat and dry it. Place two test samples and two control samples on each infected plate, with the centers of the samples at least 25 mm apart and at least 15 mm from the edge of the plate. After placement, gently press them against the plate surface with sterile tweezers. Incubate upright for 16–18 hours under the specified temperature and humidity conditions. Finally, measure the inhibition zone (including the sample) with a vernier caliper. Select a fully transparent inhibition zone (the widest point in the normal direction). The diameter should be measured at the outer edge of the inhibition zone. The inhibition zone value is the average of six samples, rounded to two significant digits, and compared for final judgment.

[0070] 3. Analysis of test results of various embodiments and comparative examples Figure 2 The Vt and It plots of the flexible wearable power generation devices prepared in Examples 1-3 of the present invention and Comparative Example 1 measured at the same temperature and humidity. It can be seen that the "purple" flexible wearable power generation device prepared in Example 1 has better voltage and current output.

[0071] Figure 3 The conductivity graphs of the flexible wearable power generation devices prepared in Examples 1-3 of the present invention and Comparative Example 1 were measured at the same temperature and humidity. It can be seen that the flexible wearable power generation devices prepared in the present invention have high and stable conductivity even under temperature changes.

[0072] Figure 4 The temperature curves of the flexible wearable power generation devices prepared in Examples 1-3 of the present invention measured at the same humidity are shown. It can be seen that the asymmetric structural color (black and purple) in Example 1 (the "purple non-woven fabric" flexible wearable power generation device) exhibits a greater temperature difference than the other asymmetric structural colors (black and gold) and the asymmetric structural color (black and green), indicating a more asymmetric effect of photothermal evaporation.

[0073] Figure 5 The following are absorption spectra of the flexible wearable power generation devices prepared in Examples 1-3 and Comparative Example 1. It can be seen that the polypyrrole coating in the asymmetric structural color exhibits an absorbance of nearly 90% in the 0.5 μm to 2.5 μm wavelength range, and the different structural colors within the asymmetric structural color exhibit varying absorbance in the 0.5 μm to 2.5 μm wavelength range (absorbance scale: black > green > gold > purple), demonstrating the wide applicability of the flexible wearable power generation devices prepared in this invention for a variety of scenarios.

[0074] Figure 6This is a graph showing the number of wash cycles for the flexible wearable power generation device prepared in Example 1 of the present invention. It can be seen that after five washes, the resistance change rate is less than 20%, indicating good washability.

[0075] Figure 7 This is a diagram of the inhibition zone of the flexible wearable power generation device prepared in Example 1 of the present invention. It can be seen that the diameter of the inhibition zone is between 15 and 30 mm, indicating that the flexible wearable power generation device prepared in the present invention has good antibacterial properties.

[0076] Figure 8 A diagram showing the practical application of the flexible wearable power generation device prepared in Example 1 of the present invention.

[0077] Table 1 below summarizes the maximum V value, I value and their sustained stable time period that can be achieved by Example 1 and various comparative examples at the same humidity and temperature, and also summarizes the water resistance of Example 1 and various comparative examples.

[0078] Table 1 Test results of Example 1 and Comparative Example

[0079] The data in Table 1 show that the flexible wearable power generation device prepared in Example 1 has significant advantages over the comparative example. In particular, the ALD functional thin film layer in the present invention achieves performance enhancement through the following mechanisms: (1) constructing color asymmetry to drive evaporation-humidity gradient power generation; (2) forming a built-in electric field to enhance the electrochemical potential difference; (3) blocking environmental corrosion to maintain the conductivity of polypyrrole; and (4) enhancing the interface bonding force and mechanical durability.

[0080] The data from Comparative Example 1 shows that due to the lack of the ALD layer, the aforementioned mechanisms are ineffective, resulting in a significant drop in voltage and current. This result validates the central role of ALD technology in this invention and demonstrates the importance of structure-material-function collaborative design.

[0081] The data from Comparative Example 2 shows that the voltage and current of Comparative Example 2 (full ALD coverage) are significantly lower than those of Example 1 (partial coverage), demonstrating that color asymmetry and the heterojunction interface area are key design factors for the power generation performance of this invention. This demonstrates that structural asymmetry is essential for photothermal-evaporation humidity gradient power generation and is achieved through partial ALD coverage. The exposed heterojunction interface (direct contact between polypyrrole and Al₂O₃) is crucial for electrochemical potential difference power generation; full ALD coverage destroys the effective interface. The conductive path is preserved: the exposed polypyrrole area serves as a charge collection electrode and cannot be completely covered by the insulating ALD layer.

[0082] Data from Comparative Example 3 show that omitting the PVA cross-linking step significantly reduces the device's voltage and current output. This is attributed to: increased resistance due to a broken conductive network; weakened humidity gradient and heterojunction effects due to interface degradation; and accelerated oxidative deactivation of polypyrrole. This further demonstrates the necessity of PVA cross-linking: enhancing the bonding strength between polypyrrole and the substrate, maintaining the integrity of the conductive network; enhancing hydrophilicity to optimize humidity gradient power generation; and stabilizing the heterojunction interface. The synergistic effect of photothermal evaporation and electrochemical power generation is highly dependent on the structural support and functional modification of PVA cross-linking.

[0083] It should be noted that the present invention is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the technical solution of the present invention are all included in the technical scope of the present invention. In addition, without departing from the scope of the present invention, other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present invention.

Claims

1. A flexible wearable power generation device, characterized in that: It comprises a conductive non-woven fabric layer and an atomic layer deposition functional film layer attached to one side of the conductive non-woven fabric layer, wherein the projected area of ​​the atomic layer deposition functional film layer on the conductive non-woven fabric layer is smaller than the area of ​​the conductive non-woven fabric layer; There is a difference in heat absorption between the conductive non-woven fabric layer and the atomic layer deposition functional thin film layer with respect to solar radiation.

2. A flexible wearable power generation device according to claim 1, characterized in that: The projected area of ​​the atomic layer deposition functional thin film layer on the conductive non-woven fabric layer is 1 / 3 to 2 / 3 of the area of ​​the conductive non-woven fabric layer.

3. A flexible wearable power generation device according to claim 1, characterized in that: The structural color of the atomic layer deposition functional thin film layer is different from the structural color of the conductive non-woven fabric layer; the thickness of the atomic layer deposition functional thin film layer is 10-100 nm.

4. A flexible wearable power generation device according to claim 1, characterized in that: The conductive material of the conductive non-woven fabric layer includes polypyrrole cross-linked with polyvinyl alcohol.

5. The flexible wearable power generation device according to claim 1, characterized in that: The flexible wearable power generation device further includes a skin-friendly adhesion layer, which is adhered to a side of the conductive non-woven fabric layer away from the atomic layer deposition functional thin film layer.

6. The method for preparing the flexible wearable power generation device according to any one of claims 1 to 5, wherein: The following steps are involved: S1, pre-treating the non-woven fabric, then mixing it with a pyrrole solution, adding an oxidant to react in an ice bath, washing and drying it, then immersing it in a PVA solution, heating and cross-linking it, to obtain a conductive non-woven fabric layer; S2. Performing a single-sided atomic layer deposition process on the conductive non-woven fabric layer to obtain an atomic layer deposition functional thin film layer.

7. The method for preparing a flexible wearable power generation device according to claim 6, characterized in that: In the step S1, the pretreatment specifically comprises: ultrasonically cleaning and drying the non-woven fabric with an organic solvent, wherein the organic solvent comprises at least one of anhydrous ethanol, methanol, and propanol; The oxidant comprises at least one of ammonium persulfate, ferric chloride, potassium permanganate, and chloranil; The ice bath temperature is 0-10°C, and the reaction time is 3-5h; The temperature of the heating cross-linking is 110-130° C., and the time of the heating cross-linking is 20-40 minutes.

8. The method for preparing a flexible wearable power generation device according to claim 6, wherein: In step S2, the single-sided atomic layer deposition process is specifically as follows: placing the conductive non-woven fabric layer in an atomic layer deposition device, evacuating the device, setting the deposition temperature, and starting a deposition cycle after the temperature stabilizes. After the deposition is completed, the device is cooled to room temperature, and the sample is removed to obtain an atomic layer deposition functional thin film layer; One deposition cycle consisted of a precursor A pulse of 0.05–0.2 s, a nitrogen purge of 5–15 s, a precursor B pulse of 0.05–0.2 s, and a nitrogen purge of 5–15 s.

9. The method for preparing the flexible wearable power generation device according to claim 8, characterized in that: The vacuuming is specifically to vacuumize to a vacuum degree of 1×10 -6 ~1×10 -8 Torr; The deposition temperature is 80-150° C., and the number of deposition cycles is 100-1500; The precursor A includes at least one of trimethylaluminum, titanium tetrachloride, and diethylzinc; the precursor B includes at least one of deionized water, ozone, ammonia, and hydrazine.

10. The method for preparing a flexible wearable power generation device according to claim 6, wherein: The step S2 further includes a step S3: laminating the skin-friendly bonding layer to the side of the conductive non-woven fabric layer away from the atomic layer deposition functional film layer, and performing stitching, hot pressing and packaging to obtain the flexible wearable power generation device.